A parametric study of Proton Electrolyte Membrane (PEM) fuel cell performances - Lim, Adrian Eu Chun (2012)
A two-dimensional, steady-state and isothermal model of the proton electrolyte membrane (PEM) fuel cell has been developed numerically, using a commercial package COMSOL. The single channel cell, which consists of seven regions, is used as the computational domain. The governing equations for mass, momentum, mass transport and charge equations are coupled and solved to produce the polarization curves for the fuel cell performance. The resultant polarization curves obtained from the numerical simulation are validated by comparing with the experimental results under normal operating conditions. Further, the benchmarked numerical model is used to investigate the effect of the temperature, concentration of hydrogen, concentration of oxygen, operating pressure, stoichiometric flow ratio, channel height, gas diffusion layer (GDL) thickness, membrane thickness and GDL porosity on the performance of the PEM fuel cell. The modeling results agree reasonably well with the experimental polarization curves within allowable numerical scatter, except the mass transport region. As the fuel cell and the gas humidification temperature increases, the current density and maximum power density both increase. This trend is also observed in the concentration of hydrogen and the concentration of oxygen in air. As the concentration increases, the improvement of the fuel cell performance becomes negligible. The increase in operating pressure in both flow channels also increases both the current density and maximum power density. Between the two flow channel's operating pressure, the cathode flow channel's operating pressure plays a predominant role in affecting the performance of the fuel cell. As the stoichiometric flow ratio of hydrogen and air are increased at both flow channel inlets, the current density, the limiting current density and maximum power density increase. For the stoichiometric flow ratio of 5.0 and above, the improvement in the fuel cell performance is negligible. Further investigation shows that, the air stoichiometric flow ratio has a predominant effect in improving the performance of the fuel cell while the hydrogen stoichiometric flow ratio does not have any effect, based on the present simulation. As the channel height increases, the current density and the maximum power density increases. Above a particular height, i.e. 1mm, the improvement in the performance of the fuel cell is negligible. The increase in thickness of both GDL, reduces the current density and maximum power density.